Design and implementation of a simulation program for dna computing progresses - Zaiton, Zaimin (Universiti Malaysia Sarawak, (UNIMAS), 2010)
Deoxyribonucleic Acid or DNA computing has emerged as an interdisciplinary field that draws together chemistry, molecular biology, computer science, and mathematics. A number of DNA computing models to solve mathematical graph problem such as the Hamiltonian Path Problem (HPP), Traveling Salesman Problem (TSP), and the Shortest Path Problem (SPP), have been proposed and demonstrated. Normally, the DNA sequences used for the computation should be critically designed in order to reduce error that could occur during a computation. Overall, this project is mainly about the designing and implementation of a simulation program for DNA computing process. For this project, there are three main DNA computing processes, namely the Parallel Overlapping Assembly (POA), Polymerase Chain Reaction (PCR) and Graduated Polymerase Chain Reaction process. These simulations are developed using Microsoft Visual Basic 6.0 software to yield the output and perform for each processes. The output simulation will be saving in simulation output file in database created using Microsoft Access. This project provides several advantages in terms of user friendly and it is not a time-consuming process as the user can get the faster result as well,